Effects of Curcumin on the Renal Toxicity Induced by Ochratoxin A in Rats - Sara Damiano; Emanuela Andretta; Consiglia Longobardi; Francesco Prisco; Orlando Paciello; Caterina Squillacioti; Nicola Mirabella; Salvatore Florio; Roberto Ciarcia (MDPI AG, 2020)
Ochratoxin A (OTA) is a powerful nephrotoxin and the severity of its damage to kidneys depends on both the dose and duration of exposure. According to the scientific data currently available, the mechanism of action still is not completely clarified, but it is supposed that oxidative stress is responsible for OTA-induced nephrotoxicity. Bioactive compound use has emerged as a potential approach to reduce chronic renal failure. Therefore, curcumin (CURC), due to its therapeutic effects, has been chosen for our study to reduce the toxic renal effects induced by OTA. CURC effects are examined in Sprague Dawley rats treated with CURC (100 mg/kg), alone or in combination with OTA (0.5 mg/kg), by gavage daily for 14 days. The end result of the experiment finds rats treated with OTA show alterations in biochemical and oxidative stress parameters in the kidney, related to a decrease in the Glomerular Filtration Rate (GFR). Conversely, the administration of CURC attenuates oxidative stress and prevents glomerular hyperfiltration versus the OTA group. Furthermore, kidney histological tests show a reduction in glomerular and tubular damage, inflammation and tubulointerstitial fibrosis. This study shows that CURC can mitigate OTA-induced oxidative damage in the kidneys of rats.